Identification of σ(E)-Dependent Promoter Upstream of clpB from the Pathogenic Spirochaete Leptospira interrogans by Applying an E. coli Two-Plasmid System - Kędzierska-Mieszkowska, Sabina (Int J Mol Sci, 2019)
There is limited information on gene expression in the pathogenic spirochaete Leptospira interrogans and genetic mechanisms controlling its virulence. Transcription is the first step in gene expression that is often determined by environmental effects, including infection-induced stresses. Alterations in the environment result in significant changes in the transcription of many genes, allowing effective adaptation of Leptospira to mammalian hosts. Thus, promoter and transcriptional start site identification are crucial for determining gene expression regulation and for the understanding of genetic regulatory mechanisms existing in Leptospira. Here, we characterized the promoter region of the L. interrogans clpB gene (clpB(Li)) encoding an AAA(+) molecular chaperone ClpB essential for the survival of this spirochaete under thermal and oxidative stresses, and also during infection of the host. Primer extension analysis demonstrated that transcription of clpB in L. interrogans initiates at a cytidine located 41 bp upstream of the ATG initiation codon, and, to a lesser extent, at an adenine located 2 bp downstream of the identified site. Transcription of both transcripts was heat-inducible. Determination of clpB(Li) transcription start site, combined with promoter transcriptional activity assays using a modified two-plasmid system in E. coli, revealed that clpB(Li) transcription is controlled by the ECF σ(E) factor. Of the ten L. interrogans ECF σ factors, the factor encoded by LIC_12757 (LA0876) is most likely to be the key regulator of clpB gene expression in Leptospira cells, especially under thermal stress. Furthermore, clpB expression may be mediated by ppGpp in Leptospira.